Studies on the correction of calligraphic dysgraphia in schoolchildren with intellectual disabilities - Santana del Sol, Yisel (2021)
This articleanalyzes theoretical aspects related to the correction of calligraphic dysgraphia, as well as the characteristics of schoolchildren with intellectual disabilities with this type of disorder. Existing theories and conceptions about correcting calligraphic dysgraphia were reviewed, identifying the flaws or symptoms presented by these schoolchildren with intellectual disabilities. For a quality education, it is convenient to point out, the importance of comprehensive educational care for students with specialeducational needs in written communication, hence the need to prepare them to correct writing disorders, which require methods and alternatives specialized, depending on their development.The criterion of practice, through the use of actions in the school and the criterion of experts, allows to guarantee its possibility, aptitude and value to originate the changes that the transformations require at the level and develop the integral education of the new man.